Employability and the Bologna Process - Saraiva, Margarida (2012)
After the implementation of the Bologna Process in Portuguese higher education institutions, it’s necessary to start looking at some of its first consequences. The Bologna Process is now an integral part of the lexicon of reference of the whole European higher education. Although knowledge continues to be transmitted by the traditional way, Bologna covers qualifying new perspectives, generate changes of emphasis, including the Teaching for Learning and Education Training. Competitiveness, employment, labor market, etc. are concepts which are gradually internalized by the higher education institutions. In Portugal, with the adequacy of the various courses to the Paradigm of Bologna, the higher education institutions do not intend to offer students a mere system of training / education but different learning approaches and a set of skills that allow an easier insertion on the labor market. The enormous competitive advantages are the improved intellectual and cultural skills, associated to the capacity building initiative, adaptability, flexibility and communication. It is essential to reorient the provision of academic qualifications, focusing on courses tailored to the needs of the economy and society. That goal will be achieved if the connection between higher education institutions and the business world is strong. In this sense, it was essential to understand and analyze the adequacy of scientific training taught by the University of Évora to the graduates, in relation to the profession and occupational mobility, in line with the new European Space for Higher Education. In order to complete this study, it was carried out a questionnaire survey applied to graduate students who attended the Masters in Economics and Business in the University of Évora, having been obtained the following results: • The people who attend the courses of the 2nd Cycle are mostly young, female, and continues his/hers graduate studies at the same school where he earned a degree. • The younger respondents are not available to go on mobility as it is proclaimed in the Bologna Declaration and consequently, for the construction of the European Higher Education Area. • More and more, knowledge is being taken as the crucial element to getting a job, and that lack of experience, given to the very young age of graduates, may be a barrier to employability. • In the opinion of graduates respondents, there is a proper relationship between the training received and the training required by the job market. • The expectations of graduate respondents in relation to the acceptability of the labor market were partially thwarted. • Graduates respondents hold a very reasonable knowledge of reality and actually believe in an adjustment between the expectations created around the Bologna Process and its acceptability in the job market, endorsing the new principles embedded in appropriate courses now (employability, mobility and international recognition, acquisition of new skills, etc.). Generally, this study is to obtain a contribution of all stakeholders in order to boost the reflection and debate on the subject under study. In particular, it is believed that the higher education institution involved, the labor market factors and the students will be much more able to understand this new social and European business reality. And ultimately, the results could serve as indicators for the future of professionals in the studied area.